Actuating Bimorph Microstructures with Magnetron-Sputtered Ti-Ni-Cu Shape Memory Alloy Films - Vlad Bolocan; Dragos Valsan; Aurel Ercuta; Corneliu-Marius Craciunescu (Nanomaterials, 2022)
The generation of microactuation using narrow thermal hysteresis Ti-Ni-Cu shape-memory alloy films deposited on non-metallic substrates as the active element is studied based on a model previously developed for Ni-Ti/Si bimorphs. To this end, the compositional range in which the B2 (monoclinic) → B19 (orthorhombic) martensitic phase transformation occurs was considered, and films were deposited by magnetron sputtering on heated Si and Kapton substrates. Ultra-fine grains were observed for the 550 °C deposition temperature. The selected composition was close to Ti50Ni35Cu15, so the narrowing of the thermal hysteresis is not associated with a significant reduction in shape recovery capability. The microstructure and composition of the target materials and as-deposited films used in our experiments were characterized by X-ray diffraction and scanning electron microscopy, whereas the temperature dependence of the volume fraction of the martensite phase was derived using differential scanning calorimetry records for the target materials and from the temperature dependence of the electrical resistance data for the films. An original model was used to predict the actuation of cantilever-type bimorphs with Kapton and Si substrates.